2019
DOI: 10.1017/s1049023x19004710
|View full text |Cite
|
Sign up to set email alerts
|

Developing “Herd Immunity” in a Civilian Community Through Incorporation of “Just-In-Time” Tourniquet Application Training

Abstract: Introduction:Herd immunity, a concept normally applied in vaccinated populations, is a preventative measure to determine if a significant portion of a population can protect vulnerable individuals against a certain disease. Like vaccines, tourniquet education can be a form of herd immunity to protect vulnerable individuals in a population and prevent the loss of life from a peripheral hemorrhage. The authors have identified a deficiency in simple, quick, and effective hemorrhage control education. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…Our study suggests that a game-based computer application based on curricular objectives of COVID-19 instruction is an effective learning methodology. Other studies of games used to teach medical students have shown that serious games are comparable to lectures in terms of knowledge gains when measured immediately after learning method application, [16][17][18][19][20][21] a result which our study replicates. The advantage of gamebased learning strategies is the active participation and interaction at the center of the learning experience; lectures do not sufficiently engage the medical students.…”
Section: Figsupporting
confidence: 79%
“…Our study suggests that a game-based computer application based on curricular objectives of COVID-19 instruction is an effective learning methodology. Other studies of games used to teach medical students have shown that serious games are comparable to lectures in terms of knowledge gains when measured immediately after learning method application, [16][17][18][19][20][21] a result which our study replicates. The advantage of gamebased learning strategies is the active participation and interaction at the center of the learning experience; lectures do not sufficiently engage the medical students.…”
Section: Figsupporting
confidence: 79%
“…With the occurrence of a number of major disasters around the world over the past 40 years, including the COVID-19 pandemic, there is a growing need for disaster training [1][2][3][4][5][6][7][8][9][10][11][12]. Accordingly, various disaster medicine educational programs have been developed and their effectiveness has been tested [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…With the occurrence of a number of major disasters around the world over the past 40 years, including the COVID-19 pandemic, there is a growing need for disaster training [1][2][3][4][5][6][7][8][9][10][11][12]. Accordingly, various disaster medicine educational programs have been developed and their effectiveness has been tested [1][2][3][4][5][6][7][8][9][10][11][12]. In particular, chemical disasters, such as the Seveso dioxin leakage disaster in Italy, the methyl isocyanate leakage disaster in Bhopal, India, and the Gumi fluoric acid gas leakage disaster in Korea in 2012, have attracted a great deal of attention worldwide [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 One notable training approach is the Just in Time method, wherein laypersons are taught tourniquet application onsite during a mass-casualty event; these courses have proven effective at increasing success rates in laypersons. 28,29 Pediatric populations remain poorly examined, however, despite injury being the most common cause of morbidity and mortality in children and adolescents world-wide. [30][31][32][33] Some studies have demonstrated the effectiveness of commercially available tourniquets when applied on children as young as 2 years old, both in military and civilian settings.…”
mentioning
confidence: 99%